Comparison of visual and auditory emotion recognition in patients with cerebellar and Parkinson´s disease. (4th March 2019) - Adamaszek, Michael; D'Agata, Federico; Steele, Christopher J.; Sehm, Bernhard; Schoppe, Cornelia; Strecker, Karl; Woldag, Hartwig; Hummelsheim, Horst; Kirkby, Kenneth C.
ABSTRACT: Widespread cortical-subcortical networks are involved in the recognition and discrimination of emotional contents of facial and vocal expression, whereby the cerebellum and basal ganglia are two subcortical regions implicated in these networks with limited evidence to their specific contributions. To investigate this we compared patients with circumscribed cerebellar lesions and patients with Parkinson's disease (PD) on an approved test battery. We studied two groups with subcortical disease, focal cerebellar infarction (n = 22) and PD (n = 22), and a neurological control group with focal supratentorial ischemia (SI) (n = 16) were. Assessments were according to inpatient protocols for neuropsychological routine evaluation, including tests of memory, executive function and attention. Participants completed the Tuebingen Affect Battery, a recognized measure of recognition and discrimination of facial and vocal expression of emotion. As a result, cerebellar lesions were associated with greater impairment than PD and SI in recognition and discrimination of cues of both facial and vocal expressions of differing basic emotions. No confounding effect of other cognitive domains, particularly executive function and attention, was found. Taken together, our findings suggest a specific contribution of the cerebellum to cerebral networks that process facial and vocal emotion expression, related to rapid decisions regulating appropriate behavioral responses in social environments.